Molecular structure and paramagnetic properties of bis-diisobutyldithiophosphinate complexes of Europium(III), Ytterbium(III) and Lutetium(III) with 2,2-bipyridyl using NMR; Polyhedron; Vol. 134 - Babailov S. P. Sergey Pavlovich; Zapolotsky E. N. Evgeny Nikolaevich; Fomin E. S. Eduard Stanislavovich; Qu Ya. Yanyang (2017, 2017)
Title screen